La infografía como estrategia didáctica para el aprendizaje del área de ciencias sociales en los estudiantes del primer grado de educación secundaria del colegio Cooperativo César Vallejo 2022 - Cordova Egoavil, Julissa Lucero (2023)
The central purpose of the research was to evaluate the effect of infographics as a teaching strategy on improving social studies learning among secondary school students at an educational institution in the city of Iquitos. The research was explanatory, with a quasi-experimental pre- and post-test design and intact groups. The population consisted of 124 students, and the sample consisted of 62 first-year secondary school students, divided into a control group (31 in classroom C) and an experimental group (31 in classroom A). The sampling was non-probabilistic and non-random, as it was chosen intentionally and for convenience. Data collection was conducted using a pre- and post-test instrument, the purpose of which was to determine the development of the competency "constructing historical interpretations." The most important results, with a U = 871 and p-value < 0.001, show significant evidence of differences between the groups analyzed. It is concluded that the use of infographics as a teaching strategy significantly improves the learning of the competency "Constructing Historical Interpretations" in the area of Social Sciences among first-year secondary school students at Colegio Cooperativo Cesar Vallejo 2022.